2014
DOI: 10.1080/07399332.2014.909432
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Chinese Female Sex Workers From Their Stable Partners: A Hierarchical Multiple Regression Analysis

Abstract: Limited data are available regarding risk factors that are related to intimate partner violence (IPV) against female sex workers (FSWs) in the context of stable partnerships. Out of the 1,022 FSWs, 743 reported ever having a stable partnership and 430 (more than half) of those reported experiencing IPV. Hierarchical multivariate regression revealed that some characteristics of stable partners (e.g., low education, alcohol use) and relationship stressors (e.g., frequent friction, concurrent partnerships) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 33 publications
2
18
2
2
Order By: Relevance
“…The effect was not as strong as FSWs' own alcohol use, though. Our results are consistent with a positive relation between primary partner alcohol use and IPV (Zhang et al, 2015) among Chinese FSWs and with those of several studies among non-FSWs (Dunkle et al, 2006;Sabri, Renner, Stockman, Mittal, & Decker, 2014;Weinsheimer, Schermer, Malcoe, Balduf, & Bloomfield, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The effect was not as strong as FSWs' own alcohol use, though. Our results are consistent with a positive relation between primary partner alcohol use and IPV (Zhang et al, 2015) among Chinese FSWs and with those of several studies among non-FSWs (Dunkle et al, 2006;Sabri, Renner, Stockman, Mittal, & Decker, 2014;Weinsheimer, Schermer, Malcoe, Balduf, & Bloomfield, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that in terms of IPV risk, the exact frequency of drinking, especially beyond the occasional level, was less important than whether the FSW consumed any alcohol at all. These results are different from Zhang et al (2015), who found that Chinese FSWs who consumed alcohol were not significantly more likely to report IPV than FSWs who never drank, but are in line with several studies among the general population that have documented a link between a woman's alcohol use and IPV (see Devries et al, 2014). We could not determine from our survey data whether alcohol use is modifying the FSWs' coping skills as it does in their interaction with clients, or whether the effect is driven by other dynamics, such as the FSWs drinking as a way of coping with anticipated violence from their primary partner whom they cannot as easily escape or avoid as they can a client.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This was associated with lower SRH knowledge and poorer service utilisation. Research with other Chinese FSWs has found the proportion ever experiencing violence to range from 16% to 58%[ 43 45 ]. Sexual and gender-based violence against FSWs is a pervasive and complex issue, and addressing this requires input from multiple sectors including the community, health, police and legal sectors.…”
Section: Discussionmentioning
confidence: 99%
“…El rol como prostituta se opone a los mandatos sociales que marcan el comportamiento sexual femenino socialmente aceptado. Así, por ejemplo, en China (Zhang et al, 2015), para ser aceptadas, las mujeres tienen que ser amables, pasivas y sexualmente inocentes. En India (Pandiyan, 2014), es incompatible la aceptabilidad social con el sexo prematrimonial.…”
Section: Descripción Del Estigma De Prostitutaunclassified